2022
DOI: 10.5688/ajpe8562
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Journal Club Activities Versus Clinical Debate Activities in Pharmacy Experiential Education

Abstract: Objective. Within pharmacy experiential education, practicing literature evaluation skills usually occurs via journal clubs. Clinical debates have gained traction as an engaging alternative during advanced pharmacy practice experiences (APPEs). The purpose of this study was to compare clinical knowledge and literature evaluation application between journal clubs and clinical debates during APPEs. Methods. This mixed-methods prospective study was conducted in fourth year pharmacy students completing inpatient g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Preceptors can even consider other tactics, such as clinical debates, to meet the needs of the learners and introduce the opportunity to review new literature. 18 In addition, pharmacists who have formal teaching responsibilities, such as lecturing at a college of pharmacy, need to design and routinely update their materials. This includes evaluating new literature, such as guideline updates or clinical trial findings, to address in their presentations.…”
Section: Precepting and Teachingmentioning
confidence: 99%
“…Preceptors can even consider other tactics, such as clinical debates, to meet the needs of the learners and introduce the opportunity to review new literature. 18 In addition, pharmacists who have formal teaching responsibilities, such as lecturing at a college of pharmacy, need to design and routinely update their materials. This includes evaluating new literature, such as guideline updates or clinical trial findings, to address in their presentations.…”
Section: Precepting and Teachingmentioning
confidence: 99%
“…10 The use of debates during APPEs as an alternative to journal clubs during APPEs is not well studied. 16,17 Toor et al concluded debates could be employed to teach literature evaluation skills, but some participants reported they had not completed a journal club therefore a fair comparison was impossible. 16 Recently, Steuber and colleagues found no differences in knowledge scores among participants who participated in both debates and journal clubs.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, Steuber and colleagues found no differences in knowledge scores among participants who participated in both debates and journal clubs. 17 Nonetheless, debates during experiential education can be considered as an alternative to journal clubs; however impediments may include higher faculty workload and time commitment, a lack of evaluation tools, and potential difficulty in judging student performances to provide meaningful feedback. 7 Debates in pharmacy education have traditionally been conducted with students debating fellow classmates within the same institution.…”
Section: Introductionmentioning
confidence: 99%